Genetic disorders of thyroid development, hormone biosynthesis and signalling. (5th September 2022) - Moran, Carla; Schoenmakers, Nadia; Visser, W. Edward; Schoenmakers, Erik; Agostini, Maura; Chatterjee, Krishna
Abstract: Development and differentiation of the thyroid gland is directed by expression of specific transcription factors in the thyroid follicular cell which mediates hormone biosynthesis. Membrane transporters are rate‐limiting for cellular entry of thyroid hormones (TH) (T4 and T3) into some tissues, with selenocysteine‐containing, deiodinase enzymes (DIO1 and DIO2) converting T4 to the biologically active hormone T3. TH regulate expression of target genes via hormone‐inducible nuclear receptors (TRα and TRβ) to exert their physiological effects. Primary congenital hypothyroidism (CH) due to thyroid dysgenesis may be mediated by defects in thyroid transcription factors or impaired thyroid stimulating hormone receptor function. Dyshormonogenic CH is usually due to mutations in genes mediating thyroidal iodide transport, organification or iodotyrosine synthesis and recycling. Disorders of TH signalling encompass conditions due to defects in membrane TH transporters, impaired hormone metabolism due to deficiency of deiodinases and syndromes of Resistance to thyroid hormone due to pathogenic variants in either TRα or TRβ. Here, we review the genetic basis, pathogenesis and clinical features of congenital, dysgenetic or dyshormonogenic hypothyroidism and disorders of TH transport, metabolism and action.